A COMPARATIVE STUDY ON QUANTITATIVE ESTIMATION OF TANNINS IN TERMINALIA CHEBULA, TERMINALIA BELERICA, TERMINALIA ARJUNA AND SARACA INDICA USING SPECTROPHOTOMETER - Saxena, Vasundhara; Mishra, Garima; Saxena, Akash; Vishwakarma, Kamlesh Kr. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Ashoka, arjuna baheda and harde are constituents of digestive churna from old age civilization. These drugs principally contain tannins which are widespread in plant kingdom. It is a poly-phenolic compound which is proven as antioxidants and possesses a chemo- protective potential. They are found in leaves, flowers, fruits and bark. The aim of study is to estimate the amount of tannins present in these drugs using folin-denis method.Terminalia chebula (combretaceae) (harde), Terminalia belerica (combretaceae)(bahera), Terminalia arjuna (combretaceae)(arjuna) and Saraca indica (leguminaseae) (ashoka) were crushed to coarse powder. The alcoholic extracts of the drugs were prepared for photometric determination of tannins using folin-denis method. The tannin concentration was determined by the standard graph of tannic acid solution and was found to be 99.55456mg/gm,9.95568mg/gm, 54.96288mg/gm, and 57.4869 mg/gm for harde, arjuna, baheda and ashoka respectively. The concentration curve for tannic acid was determined and the correlation coefficient was calculated and was found to be 0.998 which indicates the good linearity between the concentration and the absorbance. It has been found that the tannins form the stable complexes with protein, starch and metal chelates by disturbing the metabolic activity of the bacterial enzymes nutrient availability, and functionality of biological membranes. The present study can be used as one of the parameters for standardization of medicinal plants.